The Influence of Financial Statement Audit and The Role of Internal Audit on the Quality of Financial Reporting - Liza Seftina; Renny Maisyarah (Journal of Management and Business Analytics, 2025)
This study aims to analyze the influence of external financial statement audits and the role of internal audit on the quality of financial reporting within an organization. The quality of financial reports is a critical factor in ensuring transparency, accountability, and informed decision-making by stakeholders. Both external and internal audits play strategic roles in enhancing the credibility and reliability of financial statements.A quantitative approach is used in this research, employing multiple regression analysis. Data were collected through questionnaires distributed to finance staff and internal auditors in various public and private sector companies. The independent variables in this study are financial statement audit (X₁) and internal audit role (X₂), while the dependent variable is the quality of financial reporting (Y). The findings indicate that financial statement audits have a positive and significant effect on financial reporting quality. Similarly, the role of internal audit also shows a significant influence, where the more effective the internal audit function is, the higher the level of accuracy and reliability of the financial reports. These results emphasize the importance of synergy between external and internal auditors in maintaining the integrity of corporate financial reporting.